Instructional design of the subject General Psychology in its virtual modality - Yaritza García Ortiz; Idalmis Ramirez Oves; Yurianely Machado Machado; Delia Maria Santiesteban Pineda; Yanexy Valdés Garciga; Omar Cruz Martín (Edumecentro)
Background: instructional design is the planning, preparation and design of the resources and environments necessary for learning to take place. In blended and distance learning modalities, it is necessary to harmoniously combine didactic and technological requirements. Objective: prepare the instructional design of the General Psychology subject in its virtual modality. Methods: an educational research was carried out at Villa Clara University of Medical Sciences from September 2022 to April 2023, following the action research method and organized by the phases proposed by Chiape for the instructional design of a course: analysis of key factors, instructional design, production of learning resources and issuance. The analytical-synthetic and inductive-deductive methods were used as theoretical methods; and empirical: documentary analysis, survey of specialists and focus group technique. Results: based on the focal groups, decisions were made for the instructional design of the subject in its virtual modality, which was distributed into 10 topics, each with a study guide and an extra-class task. The study guides made reference to the importance of the content for the doctor's professional performance and provided strategies to organize the study. In the extra-class tasks, reflective and interpretive questions and problem situations were used. Conclusions: the instructional design of the General Psychology subject in its virtual modality satisfactorily links the technological and pedagogical dimension, according to the assessment made by the specialists.